학생운동선수의 생활환경 실태조사: 테니스선수를 중심으로 - 오재민(Jae-Min OH); 박재현(Jae-Hyeon PARK); 김혜진(Hyeoi Jin KIM) (한국체육측정평가학회지, 2022)
이 연구는 학생테니스선수가 학교생활 및 운동생활을 하며 보편적으로 관계를 맺고 있는 전반적인 생활환경에 대해 어떻게 인식하고 있는지 실태를 확인하고 개인의 특성에 따른 인식의 차이를 확인하는 것이 목적이다. 국내중·고등학교에 재학 중인 학생테니스선수를 연구대상으로 선정하였으며, 편의표집추출방법을 사용하여 160명의 자료중 응답거절 및 무응답, 불성실 자료를 제외한 155명을 최종연구대상자로 선정하였다. 학생테니스선수들의 운동 환경인식에 대한 실태를 조사하기 위하여 설문지는 학습, 지도자와의 관계, 교우 및 팀원과의 관계, 훈련 및 대회관련환경을 측정하는 4개요인 37문항, 5점 척도로(매우 그렇다, 그렇다, 보통이다, 아니다, 전혀 아니다) 구성하였다. 설문은구글 설문지를 이용하여 조사를 실시하였으며, 수집된 자료는 MS-Excel을 이용하여 정리하였다. 자료처리를 위해IBM SPSS 25.0을 이용하여 기술통계분석과 Chi-squared test (x²)를 실시하였으며, 모든 통계적 유의수준은 a=.05로설정하였다. 이 연구의 결과는 다음과 같다. 학생테니스선수의 ‘학습관련 인식’에서는 3번문항(χ2 =22.72, p=.000), 9번문항(χ2 =18.593, p=.001), 10번 문항(χ2 =11.193, p=.024) 등에서 중학생이 고등학생에 비해 긍정적으로 인식하고있는 것으로 나타났으며, ‘지도자와의 관계 관련 인식’에서는 전반적으로 남학생이 여학생에 비해 지도자에 관해 긍정적으로 인식하고 있는 것으로 나타났다. ‘교우 및 팀원과의 관계 관련 인식’에서는 2번문항(χ2 =16.18, p=.001)에서만중학생이 긍정적으로 인식하고 있으며, ‘훈련 및 대회관련 인식’에서는 2번문항(χ2 =8.457, p=.037)과 4번문항(χ 2 =12.216, p=.016)에서 남학생이 여학생에 비해 긍정적으로 인식하고 있는 것으로 나타났다. 전반적으로 상급학교진학 등에 부담감이 적은 중학생이 고등학생에 비해 학습이나 교우 관계에서 긍정적인 인식을 하고 있는 것을 알수 있는 있으며, 여학생들이 지도자와 훈련 등에서 어려움을 느끼는 것을 알 수 있다. 또한 학생운동선수들은 공부에대한 필요성은 느끼지만 운동과 병행하는 것에 대한 어려움을 겪고 있는 것을 알 수 있다. 이러한 결과는 추후 학생운동선수들을 이해하고 지도하는데 있어 도움이 될 것으로 판단된다. The purpose of this study is to investigate the actual conditions of learning, relationships with leaders, relationships with companions and team members, training, and competition-related environments in which student tennis athletes have relationships in school and exercise. Specifically, it was intended to check how student tennis players perceived learning, relationships with leaders, relationships with companions and team members, training, and competition-related environments, and to see if there were differences in perceptions according to individual characteristics. Student tennis players enrolled in middle and high schools in Korea were selected as the subjects of the study. Data of 160 people were collected using the convenience sampling extraction method, and 5 people submitted response rejection, non-response, and unfaithful data, and 155 people were selected as the final study subjects. In order to investigate the reality of student tennis athletes' perception of the sports environment, the questionnaire consisted of 37 questions and 5 points (defiantly, yes, normal, no, never) measuring the environment related to learning, leaders, companions and team members. The survey was conducted using the Google questionnaire, and the collected data were organized using MS-Excel. Descriptive statistical analysis and Chi-square test (χ²) were conducted using IBM SPSS 25.0 for data processing. At this time, all statistical significance levels are a=.It was set to 05. The conclusions obtaind from the results of this study are as follows. It was found that there were differences in learning-related perceptions according to the personal characteristics of student tennis players, and there were no significant differences in perceptions related to leaders, companions and team members, training, and competitions. This shows that there are differences in what student athletes perceive according to their personal characteristics in questions related to learning. Specifically, it was found that student athletes felt the need to study, but had difficulty in parallel with exercise. KCI Citation Count: 0